Analisis Pengaruh Kualitas Layanan dan Kemudahan Dalam Penggunaan Aplikasi Terhadap Kepuasan Pengguna BRImo KCP Cibubur - Mitana, Mitana Nur Pitriani; Yuliantari, Kartika (Jurnal Administrasi Bisnis, 2024)
This study aims to determine the influence of service quality and ease of use on BRImo user satisfaction. The method used in this research is quantitative statistics with data collection through the distribution of questionnaires to 100 respondents. Based on the analysis of data through SPSS 26 through the t( persial) test where the t value is calculated > t table, this indicates that the service quality variable (X1) does not have a significant influence on user satisfaction (Y) and the ease of use variable (X2) does not have a significant influence on user satisfaction (Y) of the BRImo application. Based on the results of the f test (simultaneous), the two variables, namely service quality (X1) and ease of use (X2), simultaneously affect the satisfaction of BRImo application users. Keyword: Service Quality, Ease of Use, and User Satisfaction